Chronic Kidney Disease Severity Is Associated With Selective Expansion of a Distinctive Intermediate Monocyte Subpopulation - Naicker, Serika D.; Cormican, Sarah; Griffin, Tomás P.; Maretto, Silvia; Martin, William P.; Ferguson, John P.; Cotter, Deirdre; Connaughton, Eanna P.; Dennedy, M. Conall; Griffin, Matthew D. (Frontiers in Immunology, 2018)
Chronic kidney disease (CKD) affects 11-13% of the world’s population and greatly increases risk of cardiovascular disease (ASCVD) and death. It is characterized by systemic inflammation and disturbances in the blood leukocytes that remain incompletely understood. In particular, abnormalities in the numbers and relative proportions of the three major monocyte subsets - classical, intermediate and non-classical – are described in CKD and end-stage renal disease. In this study, we characterized absolute numbers of blood leukocyte subtypes in adults with renal function varying from normal to advanced CKD. The primary aim was to identify monocyte subpopulations that associated most closely with current estimated glomerular filtration rate (eGFR) and subsequent rate of eGFR decline. Leucocyte and monocyte populations were enumerated by multi-colour flow cytometry of whole blood and peripheral blood mononuclear cell (PBMC) samples from adults with CKD stage 1-5 (n=154) and healthy adults (n=33). Multiple-linear regression analyses were performed to identify associations between numbers of leucocyte and monocyte populations and clinical characteristics including eGFR and rate of eGFR decline with adjustment for age and gender. In whole blood, total monocyte and neutrophil, but not lymphocyte, numbers were higher in adults with CKD 1-5 compared to CKD 0 and were significantly associated with current eGFR even following correction for age. In PBMC, classical and intermediate monocyte numbers were higher in CKD 1-5 but only intermediate monocyte numbers were significantly associated with current eGFR in an age-corrected analysis. When intermediate monocytes were further sub-divided into those with mid- and high-level expression of class II MHC (HLA-DRmid and HLA-DRhi intermediate monocytes) it was found that only DRhi intermediate monocytes were increased in number in CKD1-5 compared to CKD 0 and were significantly associated with eGFR independently of age among the total (CKD 0-5) study cohort as well as those with established CKD (CKD 1-5). Furthermore, blood number of DRhi intermediate monocytes alone proved to be significantly associated with subsequent rate of renal functional decline. Together, our data confirm neutrophil and monocyte subset dysregulation in CKD and identify a distinct subpopulation of intermediate monocytes that is associated with higher rate of loss of kidney function.